Transformation of Organizational Models and Structures in the Digital Era: A Systematic Literature Review - Dessy Marlina; Yana Setiawan; Janah Sojanah (Yayasan Darussalam Bengkulu, 2026)
Background: Digital transformation has fundamentally changed the global business landscape and the strategic direction of modern organizations. Therefore, this study aims to identify the transformation of organizational models and structures in the digital era. Method: The method used in this study is a Systematic Literature Review with research stages following the PRISMA approach. The research data consists of 30 articles sourced from Google Scholar, Elsevier/ScienceDirect, and Garuda Dikti, covering the period 2020–2025. Results: The findings indicate that organizational models and structures in the digital era are shifting from traditional hierarchical forms to adaptive, collaborative, and agile structures that enable rapid responses to environmental changes. Digital leadership and organizational culture emerge as key success factors, with leaders acting as agents of change and an innovative culture supporting the internalization of values such as collaboration and continuous learning. The study further found that digital capabilities including digital platforms, AI, and data analytics play a dual role as catalysts for efficiency and drivers of innovation, improving data-driven decision-making and overall organizational performance. An effective digital transformation strategy requires integrated management of digital maturity, adaptive governance, and change risk management, enabling organizations to balance operational efficiency with continuous innovation. Conclusion: This research confirms that organizational transformation in the digital era is an adaptive process that requires synergy between structure, culture, leadership, digital capabilities, and strategy to achieve long-term success.